Lessons Learnt from the United States Air Force during a Joint Exercise at an Indian Air Force Transport Base - Mohin M. Sakre; Manohar Dutt; Dhiraj Jhamb (Journal of Marine Medical Society)
Introduction: Combat Operations Preparedness Exercise 2023 was held between the United States Air Force (USAF) and the Indian Air Force (IAF) with the objective of enhancing the operational readiness of both countries in regard to various aspects of Aerial Combat. Lessons Learnt: Various aspects of Aerial Combat and op-readiness were deliberated and discussed such as Tactical Combat Casualty Care, Subject Matter Expert Exchanges on several topics such as chemical, biological, radiological, and nuclear(CBRN), Fitness Classification in the USAF, decompression sickness (DCS), high altitude, and hypoxia. Aeromedical evacuation configurations were also demonstrated on board the C130J and C17. A mass casualty evacuation (CASEVAC) drill was also conducted on one of the Detachments of the base where medical teams from both countries evacuated simulated patients of varying severity on board the US aircraft. This article has brought out the lessons learned from the abovementioned lectures, discussions, and demonstrations. The knowledge gained was varyingly utilitarian such as the different practices of CASEVAC in the USAF and updated practices in CBRN disaster preparedness, different approaches in regard to DCS, high altitude, and hypoxia prevention and treatment. The IAF medical team also had the opportunity of sharing the gamut of their working and practical experiences with their US counterparts that made us efficient in our element. The US airforce personnel were impressed with the concept and workings of the Station Health Organisation. Such an organisation directed towards preventive health care and promotion of positive health is not in vogue in the USAF health care setups. The assimilated patient transport unit (PTU) of the base and the vertical litter stretcher setup of the C130 as practiced in the 87 Squadron was also palatable to the USAF personnel. Conclusion: The article finally concludes with recommendations that can be practically implemented in the IAF. It mentions enhancements in areas such as the PTU, CASEVAC/medical evacuation, parajumping practices, modernization of battle casualty care, and improved CBRN practices.